PRE-TRIAL DETENTION OF CHILDREN: EUROPEAN STANDARDS AND CROATIAN LAW (EU and comparative law issues and challenges series (ECLIC), 2019)
This paper deals with the issue of pre-trial detention of children in criminal proceedings from the aspect of European standards established under the competence of the European Court of Human Rights and the EU law, as well as from the aspect of Croatian criminal procedure law. Authors will first provide a short overview of international documents pertaining to the issue of deprivation of liberty of children. Furthermore, they will analyse the relevant case law of the European Court of Human Rights, especially the recent one. In several cases, ECHR established a violation of Art. 5 because pre-trial detention had not been used as a measure of last resort i.e., domestic courts did not take into account the applicants’ young age when deciding on pretrial detention. Hence, special attention in the paper will be given to the provisions of Directive 2016/800/EU on procedural safeguards for children who are suspects or accused persons in criminal proceedings. Articles 10 to 12 of the Directive emphasise the ultima ratio nature of detention, the need for a periodic judicial review of the decision, the availability of alternative decisions and specific treatment regarding the separation of children from adults, health care, education and family life. The adequacy of the measure of pre-trial detention for children has recently been discussed in the Croatian judicial practice regarding the case of a fourteen-year old child accused of aggravated murder. The issue of national law on pre-trial detention is especially relevant in the context of the need to transpose Directive 2016/800. Consequently, the authors will critically examine the Croatian legislation and practice and their compliance with the European standards on pre-trial detention.